Employee Sustainable Intervention Program for the Department of Social Welfare and Development: The Case of Regional Office V - Mangampo, Jinky (Journal of Interdisciplinary Perspectives, 2025)
Human resource management faces rapid changes due to societal and technological shifts, impacting workplace dynamics. In the public sector, voluntary resignations disrupt service continuity and performance, challenging agencies like the Department of Social Welfare and Development Regional Office V (DSWD RO V) in the Philippines. This study addresses a critical gap in understanding and addressing employee turnover in public sector organizations by designing an intervention program focused on improving retention, job satisfaction, and workplace support in alignment with the agency’s mission of service excellence. The study used a mixed-method approach to collect data from surveys and interviews with DSWD RO V employees, management, and former staff. Results revealed key turnover drivers, including poor work-life balance, job insecurity, limited career growth, insufficient recognition, uneven workloads, and inadequate resources. The study recommends implementing integrated retention strategies to address these factors and promote a sustainable, employee-centered environment. The findings contribute significantly to the field by offering actionable solutions for public sector organizations facing similar challenges. Implementing these strategies will strengthen DSWD RO V’s workforce and enable it to achieve its mission more effectively. Furthermore, this study provides practical implications for organizational policy and enriches the broader discourse on human resource management in the public sector.